1997
DOI: 10.1021/np960506o
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactones and Thymol Esters from Vicoa pentanema

Abstract: The aerial parts of Vicoa pentanema yielded four new sesquiterpene lactones, namely, 10α-hydroxy-14H-inuviscolide (1), 4α,5α-epoxy-10α,11β,13H,14H-1-epi-inuviscolide 3-β-d-glucoside (2), 2α-O-acetyl-3β-hydroxyalantolactone (3), and 2α,3α-dihydroxyalloalantolactone (4). The structure and stereochemical assignments of all sesquiterpenes were based on their 1H and 13C-NMR spectral data, including those derived from 2D-NMR COSY, HETCOR, FLOCK, and NOESY experiments, as well as extensive NOE-difference studies. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Ray florets 12-24, much longer than involcure and disc florets scanty. Many compounds have been isolated from P. indicum namely, sesquiterpenevicolides, monoterpenediol-vicodiol and thymol esters (Saradha Vasanth et al 1990;Mossa et al 1997), cis-cis germacranolide (Sawaiker et al 1998), 4,5,6-trihydroxy-4-7-dimethoxy flavone (Krishnaveni et al 1997). Vicolide D showed abortifacient and antifertility activities (Alam et al 1989).…”
mentioning
confidence: 99%
“…Ray florets 12-24, much longer than involcure and disc florets scanty. Many compounds have been isolated from P. indicum namely, sesquiterpenevicolides, monoterpenediol-vicodiol and thymol esters (Saradha Vasanth et al 1990;Mossa et al 1997), cis-cis germacranolide (Sawaiker et al 1998), 4,5,6-trihydroxy-4-7-dimethoxy flavone (Krishnaveni et al 1997). Vicolide D showed abortifacient and antifertility activities (Alam et al 1989).…”
mentioning
confidence: 99%
“…c Data assigned for comparison; assignment for carbon 10 of 3 was incorrectly reported by Massiot et al (1986). germacranolides (13, 14) and one elemenolide (15), from V. pentanema (Mossa et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Centrifugal preparative TLC (CPTLC, using a Chromatotron 1 instrument, Harrison Research Inc. Model 7924) was run with 4 mm silica gel PF 254 disc, using a flow rate of 2 mL/min. The isolation and structure elucidation of sesquiterpene lactones (4-15) from the aerial parts of V. pentanema was described previously (Mossa et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous phytochemical investigations of I. japonica revealed that sesquiterpenoids were the main active constituents [11] [14 -16]. To search for biologically active compounds, we investigated the chemical constituents of the aerial parts of the plant, and fourteen eudesmane sesquiterpenoids were isolated, including four new ones, (1b,5a,7b,8b,11b)-5-hydroperoxy-1-hydroxyeudesm-4(15)-eno-12,8-lactone 1 ) (1) [17], (1b,5a,7b,8b)-8-(acetyloxy)-5-hydroperoxy-1-hydroxycostic acid methyl ester 1 ) (12) [11], (1b,3b,4b,7b,8b)-1,3-dihydroxyeudesma-5,11(13)-dieno-12,8-lactone 1 ) (7) [18], (1b,3b,4b,7b,8b,11b)-1,3-dihydroxyeudesm-5-eno-12,8-lactone 1 ) (8) [18], and ten known compounds (5a)-5-hydroperoxyasperilin (2) [17], (5a)-5-hydroxyasperilin (3) [19], alantolactone (4) [11], (1b)-1-hydroxyalantolactone (5) [11] [20], (1b,11b)-11,13-dihydro-1-hydroxyalantolactone (6) [11] [21], ivangustin (9) [11], (8b)-8-hydroxysantamarin (10) [15], (1b,7b,8b)-8-(acetyloxy)-1-hydroxycostic acid methyl ester (11) [11], britannilactone (13) [22], and 1-O-acetylbritannilactone (14) [22]. To the best of our knowledge, among these known sesquiterpenoids, compounds 2 -4 were reported from I. japonica for the first time.…”
mentioning
confidence: 99%